1998
DOI: 10.1302/0301-620x.80b5.8464
|View full text |Cite
|
Sign up to set email alerts
|

Dupuytren's disease and frozen shoulder induced by treatment with a matrix metalloproteinase inhibitor

Abstract: In a series of 12 patients with inoperable gastric carcinoma who had treatment with a synthetic matrix metalloproteinase inhibitor (Marimastat) for more than one month, six developed a frozen shoulder or a condition resembling Dupuytren's disease. This suggests that the matrix metalloproteinases, a family of naturally occurring proteinases, may be involved in the pathogenesis of these two conditions. Our observation opens avenues for further research which could lead to local or systemic therapeutic interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
75
2
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(81 citation statements)
references
References 0 publications
2
75
2
2
Order By: Relevance
“…In the present study protein levels of the MMPs and TIMPs were not measured. In addition, Hutchinson et al 27 did not confirm decreased MMP:TIMP ratios (mRNA or protein) in the pathologic tissue. Further work is required to understand which mechanisms may be active.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the present study protein levels of the MMPs and TIMPs were not measured. In addition, Hutchinson et al 27 did not confirm decreased MMP:TIMP ratios (mRNA or protein) in the pathologic tissue. Further work is required to understand which mechanisms may be active.…”
Section: Discussionmentioning
confidence: 94%
“…A decreasing MMP:TIMP ratio would support ineffective degradation, and is consistent with a report regarding contracture phenomena and synthetic MMP inhibitors. Hutchinson et al 27 indicated that frozen shoulder and Dupuytren's contracture of the hand developed in 6 of 12 patients with inoperable gastric carcinoma who were given a synthetic MMP inhibitor for greater than 1 month. The inhibitor treatment would be expected to lead to a reduction in the MMP:TIMP ratio.…”
Section: Discussionmentioning
confidence: 99%
“…38 This latter study also reported a decrease in ␣-smooth muscle actin expression in the presence of the MMP inhibitor. This blockade of contraction is difficult to dovetail with the reported side effects of some of these MMP inhibitors in clinical trials in which Duputyren's-like contracture and frozen shoulder were observed [13][14][15] ; however, this may reflect the fact that culture models of collagen lattice contraction only represent a single facet of a more complex disease process. Again, drawing on the analogy with liver fibrosis, a treatment that downregulates TIMPs but increases the activity of MMPs may be an appropriate therapy for DD.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation, when reported in detail, is described as frozen shoulder or a condition resembling DD. 15 Both of these conditions involve similar fibrotic mechanisms (of the shoulder joint capsule in the case of frozen shoulder), the laying down of a collagen-rich ECM, and the involvement of myofibroblast-mediated contraction. 16,17 Although DD and frozen shoulder have different natural histories (the former a progressive disease, the latter usually self-limiting and resolving in time), they may well share common pathways leading to contracture.…”
mentioning
confidence: 99%
“…However, significant side effects from the use of MMP inhibitors have also been documented (Wojtowicz-Praga et al, 1998;Hutchinson et al, 1998;Primrose et al, 1999). Given that the b6-ERK2 interaction mediates MMP-9 secretion and that de novo expression of b6 occurs in epithelial cancer cells, inhibition of MMP activity by targetting either b6 or the ERK2 binding site may offer greater therapeutic specificity in cancer treatment than MMP inhibitors and avoid unwanted side effects.…”
Section: Discussionmentioning
confidence: 99%